Evolutionary criminology : towards a comprehensive explanation of crime - Durrant, Russil; Ward, Tony (Elsevier : Academic Press, 2015)
Theories of crime typically reflect the discipline of the theorist. There has been little attempt to construct multidisciplinary frameworks that integrate psychological, biological, and sociological concepts in explaining, and controlling, criminal activity. Evolutionary behavioral science is ideally placed to provide a comprehensive and scientifically grounded framework for understanding criminal behavior. As human beings evolved, criminal behavior was a result of adaptations, or the by-products of adaptations. This book introduces a comprehensive evolutionary behavioral science approach.